Analisis Perjanjian Kerja Laut (PKL) Terkait Waktu Kerja, Waktu Istirahat, dan Kompensasi terhadap Aturan Ketenagakerjaan di PT X - Ariibah Hanifah; Langga Lagandhy; Eka Saputra (POLITEKNIK KETENAGAKERJAAN, 2025)
This research discusses the regulation of the Seafarers’ Employment Agreement (PKL) at PT X in relation to the provisions of labor legislation. The background of this study is based on the author’s observation regarding differences between the PKL and general employment agreements. These differences relate to administrative systems and employment terms, such as working hours, rest periods, leave, and compensation. The main focus of this study is to analyze and identify the regulation of employment terms for crew members as stipulated in the PKL, based on applicable labor law provisions. This is in reference to Article 337 of Law Number 17 of 2008 on Shipping, which states that labor provisions in the shipping sector must be implemented in accordance with the prevailing labor laws. This research uses a descriptive qualitative method with data collection techniques including in-depth interviews and the study of official company documents. The results show that the PKL at PT X still refers to maritime and shipping regulations, although in practice it adopts substantive aspects of labor law. However, regulations regarding working hours, rest periods, and compensation are not elaborated in detail. This creates a potential legal vacuum in the implementation of employment relations. The study concludes that the PKL at PT X does not yet fully provide legal certainty. Therefore, it is recommended that the company explicitly and thoroughly state the rights and obligations of crew members in the PKL. Additionally, collaboration between the Ministry of Manpower and the Ministry of Transportation is needed to formulate specific regulations regarding employment relations in the shipping sector to avoid regulatory overlap.